The Relationship Between the Use Of Social Media Tiktok and Adolescent Sexual Behavior At SMAN 1 Gondang Tulungagung - Avrila Hamida Hasna; Ernawati; Samsriyaningsih Handayani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Adolescence is the most memorable period, because at this time, teenagers are prone to heartbreak, inner conflict, and misunderstanding. Dating is a common behavior among by teenagers, which may lead sexual risk behavior. Sexual behavior is related to adolescent knowledge that comes from social media that contains pornographic content that can be accessed, one of which is on Tiktok. Objectives: to determine the relationship between the use of Tiktok and adolescent sexual behavior at SMAN 1 Gondang Tulungagung Methods: Analytical observasional using cross-sectional approach to 100 teenagers as a sample in class using consecutive sampling techniques. The research time was in July - August 2024 and data collection was carried out on August 5, 2024. The independent variable in this study was the use of Tiktok social media, while the dependent variable was adolescent sexual behavior consisting of attitudes and practices. Data analysis was performed using chi-square test. Results: There were no relationship between the use of Tiktok and adolescent sexual behavior (attitude, X2 = 515, df = 2, p = 0.773); (practice, X2 = 382, df = 2, p = 0.826). There were no relationship between the use of Tiktok and adolescent sexual behavior. Conclusions: : Most of the respondents' levels of Tiktok usage were high, most of the respondents' levels of sexual behavior based on attitudes and practices were low risk, so in this study there was no significant relationship between the use of Tiktok and adolescent sexual behavior.